Design Attention System of Single Mode Aerial Fiber Optic Cable Transmission on Connection Loss on Passive Splitter - Asril, Aprinal Adila; Yolanda, Amelia; Lifwarda, -; Putri, Dwi Kemala; Kasmar, Andre Febrian (SOTVI, 2022)
In this study, a comparison of the attenuation value of single mode aerial cable with pigtail is made. Perform several types of connections using a 4 cm and 6 cm protection sleeve, with one and two connections and use a barrel adapter connector. How does the connection affect the installation of a 1:2 passive splitter device. The measuring instruments used for the measurement process are Optical Power Meter (OPM) and Optical Time Domain Reflectometer (OTDR). The attenuation value of aerial single mode optical cable is smaller than that of pigtail cable. The measurement results using OPM at a wavelength of 1310 nm, connection using a 4 cm protection sleeve, one connection, the attenuation value is 0.18525dB, this value is smaller than the pigtail cable, which is 1.2728 dB. In the installation of a passive splitter, the attenuation value on the aerial cable is smaller, namely 0.2081 dB compared to the pigtail cable, which is 4.3281. The measurement results using the OTDR obtained the connection loss value for the connection type using a 6 cm protection sleeve, one connection is smaller with a value of 0.155 dB, compared to the connection type using an adapter barrel with a value of 12,216 dB.